Evaluation of Metformin on Cognitive Improvement in Patients With Non-dementia Vascular Cognitive Impairment and Abnormal Glucose Metabolism - Lin, Yufeng; Wang, Kaiyuan; Ma, Chunchao; Wang, Xuesong; Gong, Zhongying; Zhang, Rui; Zang, Dawei; Cheng, Yan (Frontiers in Aging Neuroscience, 2018)
Objective: Recent studies have suggested that metformin can penetrate the blood-brain barrier, protecting neurons via anti-inflammatory action and improvement of brain energy metabolism. In this study, we aim to investigate the effect of metformin on cognitive function in patients with abnormal glucose metabolism and non-dementia vascular cognitive impairment (NDVCI). Methods: One hundred patients with NDVCI and abnormal glucose metabolism were randomly allocated to two groups: metformin and donepezil (n = 50) or acarbose and donepezil (n = 50). The neuropsychological status, glucose metabolism, and common carotid arteries intima-media thickness (CCA-IMT) before and after a year of treatment, were measured and compared between the groups. Results: 94 patients completed all the assessment and follow-up. After a year of treatment, there was a decrease in Alzheimer’s disease Assessment Scale-Cognitive Subscale scores and the duration of the Trail Making Test in the metformin-donepezil group. Furthermore, these patients showed a significant increase in World Health Organization-University of California-Los Angeles Auditory Verbal Learning Test scores after treatment (all P < 0.05). However, there was no obvious improvement in cognitive function in the acarbose-donepezil group. We also observed a significant decrease in the level of fasting insulin and insulin resistance index in the metformin-donepezil group, with a lower CCA-IMT value than that in the acarbose-donepezil group after a year of treatment (P < 0.05). Conclusion: We conclude that metformin can improve cognitive function in patients with NDVCI and abnormal glucose metabolism, especially in terms of performance function. Improved cognitive function may be related to improvement of insulin resistance and the attenuated progression of IMT.